Feed-based metaphylaxis programs did not affect health or performance of high-risk calves mass medicated with Draxxin on arrival - Epp, M.P.; Derstein, R.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Bovine respiratory disease continues to be the most costly disease affecting productivity and profitability in the stocker segment. Despite their high cost, longer-acting, injectable therapeutic antimicrobials such as Draxxin (Tulathromycin; Pfizer Animal Health, New York, NY) can extend the window of treatment duration, thereby reducing the incidence and severity of bovine respiratory disease. Use of feed-based metaphylaxis programs, such as therapeutic administration of multiple 5-day pulses of Aureomycin (Alpharma, Inc., Bridgewater, NJ), in conjunction with an injectable metaphylaxis program may be a cost-effective way to improve bovine respiratory disease therapy without having to physically handle and stress cattle.
Keywords: Beef; Health; Performance; Draxxin; Metaphylaxis